Productivity of varieties of spring vetch (Vicia sativa L.) in the conditions of the Southern Forest Steppe of Ukraine - Antonets, O.; Sylenko, S.; Sylenko, O.; Barylko, M. (Scientific Progress & Innovations, 2024)
Among the annual leguminous grasses, spring vetch stands out, reaching harvest maturity two months after sowing. It has nodule bacteria on the root system and is able to accumulate 60 kg/ha of biological nitrogen during the growing season. This plant improves soil fertility and is a good precursor for many crops. One of the main tasks of breeding of spring vetch is to create high-yielding varieties in terms of fodder mass and grain with high adaptive potential. Therefore, the relevance of the topic lies in the identification of promising varieties of spring vetch in the conditions of the Southern Forest Steppe of Ukraine, which are high-yielding and can be used in various directions. The purpose of research is to find out adaptive potential of varieties in the conditions of the Southern Forest Steppe of Ukraine. To achieve the goal, the following tasks must be solved: 1) to evaluate varieties of spring vetch according to the yield of seeds, green mass and hay; 2) to identify varieties that can be used in production and in breeding practice to create new competitive varieties. The research was carried out in laboratory and field conditions of the Ustymivka experimental station of plant growing of the Institute of Plant growing named after V. Ya. Yuriev of the National academy of agricultural sciences of Ukraine which belongs to the central part of the Kremenchuk district of Poltava region and the southern part of the Forest Steppe zone of Ukraine. An evaluation of 17 varieties of spring vetch was carried out for the yield of seeds, green mass and hay for the years 2021–2023. 7 varieties exceeding the Bilotserkivska 88 standard (1.9 t/ha) were selected for seed yield. 7 varieties exceeding the Bilotserkivska 88 standard (28.6 t/ha) were also selected for the yield of green mass. According to the yield of hay, 10 varieties were selected, which significantly exceeded the Bilotserkivska 88 standard (3.44 t/ha). The Bilokvitkova variety reached almost the standard level (3.47 t/ha). To realize the productivity potential of spring vetch varieties, it is necessary to take into account their ecological features. Such varieties as Polinariia, Hibrydna 85, Iaroslava and Halynka are varieties of universal direction of use. These varieties are recommended for involvement in breeding practice for the creation of new competitive varieties.